Inbound selling : how to change the way you sell to match how people buy - Signorelli, Brian (John Wiley & Sons, Inc., 2018)
"Change the way you think about sales to sell more, and sell better. Over the past decade, Inbound Marketing has changed the way companies earn buyers trust and build their brands through meaningful, helpful content. But with that change comes unprecedented access to information in a few quick keystrokes. Enter the age of the empowered buyer, one who no longer has to rely on a sales rep to research their challenges or learn more about how a companys offering might fit their needs. Now, with more than 60% of purchasing decisions made in the absence of a sales rep, the role of the rep itself has been called into question. With no end in sight to this trend, sales professionals and the managers who lead them must transform both the way they think about selling and how they go about executing their sales playbook. Expert author and HubSpot Sales Director, Brian Signorelli has viewed the sales paradigm shift from the insidehis unique insights perfectly describe the steps sales professionals must take to meet the needs of the empowered customer. In this book, readers will learn: How inbound sales grew out of inbound marketing concepts and practices A step-by-step approach for sales professionals to become inbound sellers What it really means to be a frontline sales manager who leads a team of inbound sellers The role executive leadership plays in affecting an inbound sales transformation For front-line seller, sales manager, executives, and other sales professionals, Inbound Selling is the complete resource to help your business thrive in the age of the empowered buyer"--